Tecnologias digitais e ensino de matemática: compreender para realizar. - Rocha, Elizabeth Matos (2008)
This material discusses, describes and systemizes actions for Mathematics teaching which utilizes the computer as a tool in schools. The purpose is to identify in what way is possible to integrate the computers with the Math subject, as a didactic subsidy to an education that improves results and processes of learning. The general objective of this research consists of developing some systematization strategies for a methodological education to follow along that makes the use of computers possible which integrates with the learning objectives and school programs. This is done in a way that the professor acquires autonomy and criticism with the use of this tool during the lessons, in his or her formation service during the course. In order to identify which actions of education make it possible for the integration and complementation between the Math class and the Computer Education Lab (CEL), this material, guides itself in the preparation of lessons in the continued formation of the Math professor, through the qualified and efficient use of the Computer science lab, in the actions of the school managing center, and in the possibilities and limitations of the digital technologies in our current world and in the Mathematic education, taking as methodological base theory, the Fedathi Sequence and the Didactic Engineering. The methodology used in this research applied the principles of qualitative research, characterizing itself as a participant research, in which the knowledge acquired during the practical activities in the school environment was the most important process. The research was carried through the State school of Eunice Weaver, located in Maranguape-CE. The School Managing Center, five Math professors, five students from the school who had participated as tutors and also a teacher, were directly involved in this event that occurred in a crowded Computer science Lab at the school. This idea evolved through the actions of the research included teaching which was the main purpose of learning, four groups of 6th grade and two of 9th grade from Junior High School and three groups of 10th grade from Senior High School had participated. The students were not identified and the collected quantitative data through the daily Pre-test, Re-test, participation in the didactic sessions and formularies of continued evaluation had served to understand and to base the actions developed in the planning by the professors, with the purpose of understanding, reflections and adjustments. From the entire participated groups, the professors had been the most resistant to admit that the computer can enrich and magnify the practices of education. The results proved that the strategies of education with the use of the computers, considered in this material, were based on a set of direct actions that had acted, mainly, in the human intelligence, demanding significant changes in the organization of the school, in the ergonomics of the CEL and in the thoughts and actions of the sampled researched.